Sexualités au Maghreb - Valérie Beaumont; Corinne Cauvin Verner; François Pouillon (L’Année du Maghreb)
This collection assembles ten fieldwork surveys conducted in different countries of the Maghreb (Libya, Tunisia, Algeria, Morocco, Mauritania), which seek to shed light on the conditions under which social economies of sexuality may develop, these being more diverse than might be supposed based on the “Arab-Muslim personality”. While refusing to adopt the “Orientalist” perspective (Arab-Islamic sexuality explained by the sacred texts) the “culturalist” perspective (a specifically North African way of configuring sexuality), the “moralist” perspective (societies being menaced by political islam or the “corrupted West”) and the “activist” perspective (as a defence of individual freedom, notably sexual, feminism, or political Islam), these contemporary ethnographies recreate the tensions between individualism and community ethos, between national and local dictates, between western ethics and religious proscription, all of these attracting considerable media coverage. Without pretense to exhaustivity or even to being representative of a range of real situations, these investigations nonetheless converge on one point : if all sorts of practices may be observed in the Maghreb insofar as sexuality is concerned, the parties have no intention of limiting themselves by category. Whatever the sexual preference, individuals do not necessarily use sexuality to construct an identity. In this sense, practices that are no more or less modern and pluralistic than what may be observed elsewhere, defy the normative obsession that is too often attributed to contemporary Muslim societies.